2009
DOI: 10.2136/sssaj2008.0407
|View full text |Cite
|
Sign up to set email alerts
|

Short‐Term Changes in Extractable Inorganic Nutrients during Storage of Tropical Rain Forest Soils

Abstract: The nutrient status of tropical forests is commonly assessed by measuring inorganic nutrients extracted from soil, yet samples from remote research sites may be stored for prolonged periods of time before analysis. We assessed the influence of soil storage conditions on extractable nutrients in three lowland tropical forests soils from the Republic of Panama. The soils spanned a strong rainfall gradient and contained contrasting chemical and physical properties. Storage treatments were: (i) room temperature (2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
78
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 92 publications
(82 citation statements)
references
References 39 publications
3
78
0
Order By: Relevance
“…The stability of hydrolytic enzyme activities and microbial phosphorus is in marked contrast to the rapid changes in extractable inorganic nutrients in these soils (Turner and Romero, 2009). In particular, both inorganic nitrogen (ammonium and nitrate) and phosphate concentrations changed markedly within hours of sampling when stored at either 4 C or 22 C. This means that nutrients must be extracted from soil within 24 h of sampling to ensure that values are representative of those in the field.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…The stability of hydrolytic enzyme activities and microbial phosphorus is in marked contrast to the rapid changes in extractable inorganic nutrients in these soils (Turner and Romero, 2009). In particular, both inorganic nitrogen (ammonium and nitrate) and phosphate concentrations changed markedly within hours of sampling when stored at either 4 C or 22 C. This means that nutrients must be extracted from soil within 24 h of sampling to ensure that values are representative of those in the field.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, both inorganic nitrogen (ammonium and nitrate) and phosphate concentrations changed markedly within hours of sampling when stored at either 4 C or 22 C. This means that nutrients must be extracted from soil within 24 h of sampling to ensure that values are representative of those in the field. If it can be demonstrated that enzyme activities reflect nutrient demand at a site, such assays will provide a more robust measure of nutrient status than timesensitive extractions of inorganic nutrients (Turner and Romero, 2009). …”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations